Comparison of community health nurses' preventive home visits to older adults in Sweden and Slovenia: - Marija Milavec Kapun; Nina Meglič; Senada Hajdarevic (Nurses and Midwives Association of Slovenia, 2022)
Introduction: Community health nurses contribute significantly to better health, well-being and independence of older adults. The aim of the study is to compare preventive services for older adults in community health care between Sweden and Slovenia. Methods: Literature review and document analysis were used to conduct a qualitative comparative analysis. Literature was retrieved from the MEDLINE, CINAHL and COBIB databases. An analysis of documents such as sectoral legal bases, guidelines and expert recommendations in Slovenia and Sweden was also conducted. The analysis included sources related to preventive services for older adults living at home published between January 2000 and December 2020 in Slovene, English or Swedish. Results: Twenty units of literature were included in the review. Four comparative factors were identified: system and legal basis, organisation and scope, providers, and content. In Slovenia, all older adults are entitled to the same range of preventive services. Compared to Sweden, the organisation of community health care in Slovenia is more centralised, all older adults are entitled to the same scope of preventive health visits, while the level of education and scope of competences of healthcare providers are lower. In both countries, the content of preventive home visits to older adults is similar. Discussion and conclusion: In Slovenia, community health nurses with additional knowledge could prescribe medical devices and medications form a limited list, as well as coordinate care. This would allow them to act more independently in patients' home environment. Further development of more personalised preventive services for older adults depends on research, resource provision and consideration of the organisational culture.